Republic of Estonia : Report on Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2001)
This Report on the Observance of Standards and Codes on Fiscal Transparency provides an assessment of fiscal transparency practices in Estonia. Being a leader among countries in transition, the country has achieved most of the requirements of fiscal transparency, especially in accrual accounting and fiscal management practices, which are needed to meet the demanding European Union standards for accession. There are several areas where transparency can be improved. The IMF staff has provided suggestions to improve the quality of data and fiscal reporting.